A fractional-order model for the effects of expansions in hospitals on the applicability of performance certificate programme - Beyhan Kara; Bilgen Kaymakamzade; Tugsad Tulbentci; Ahmet Savasan; David Amilo; Kamyar Hosseini (Applied Mathematics in Science and Engineering)
This study explores the impact of the Leadership in Energy and Environmental Design (LEED) certification system on healthcare services in private hospitals in North Cyprus using a fractional-order system of equations. The Near East Hospital (NEH) earned Gold-level certification with 79 points, while Burhan Nalbantoğlu Hospital (BNH) obtained 31 points. Through sensitivity analysis of indoor air quality and sustainable land criteria, the study demonstrates that hospitals adopting LEED certification provide superior service quality. The findings suggest that government hospitals could benefit from aligning with green certification criteria, potentially improving patient outcomes. Data collected from NEH and BNH support a positive relationship between green certification and increased patient and employee satisfaction, with significant evidence [Formula: see text] distinguishing LEED-certified hospitals from non-certified ones. The study also evaluates how hospital expansions affect the applicability of certification programs and the management of COVID-19, focusing on criteria such as sustainable sites, water efficiency, and indoor environmental quality. The analysis provides insights for healthcare administrators and policymakers seeking to enhance hospital infrastructure to meet certification standards, improve healthcare services, and better manage future pandemics. The research underscores the importance of green certification in improving patient care, employee satisfaction, and overall hospital performance.